A cluster randomised controlled trial comparing the effectiveness and cost-effectiveness of a school-based cognitive-behavioural therapy programme (FRIENDS) in the reduction of anxiety and improvement in mood in children aged 9/10 years - Paul Stallard; Elena Skryabina; Gordon Taylor; Rob Anderson; Obioha C Ukoumunne; Harry Daniels; Rhiannon Phillips; Neil Simpson (NIHR Journals Library, 2015)
Background: Anxiety in children is common, impairs everyday functioning and increases the risk of severe mental health disorders in adulthood, yet few children with anxiety are identified and referred for treatment. Objective: To investigate the clinical effectiveness and cost-effectiveness of a universal school-based preventative programme (FRIENDS) in reducing symptoms of anxiety and low mood. Design: Cluster randomised controlled trial. Schools (n = 41) were randomly assigned after recruitment on a 1 : 1 : 1 basis to health-led FRIENDS, school-led FRIENDS and usual school provision. Setting: Primary schools in three local education authorities in the south-west of England. Participants: Children (n = 1362) aged 9-10 years attending school and participating in personal, social and health education (PSHE). Interventions: The FRIENDS programme is a cognitive-behavioural therapy programme that develops skills to counter the cognitive, emotional and behavioural aspects of anxiety. The FRIENDS programme was led by either a trained member of the school or a health leader external to the school and was delivered over 9 consecutive weeks. The comparison group received usual school PSHE lessons. Interventions were delivered in the academic year September 2011-July 2012. Main outcome measures: Clinical effectiveness assessed by child report of symptoms of anxiety (Revised Child Anxiety and Depression Scale, RCADS); cost-effectiveness based on RCADS and quality-adjusted life-years (Child Health Utility 9 Dimensions, CHU-9D) between baseline and 6 months; process evaluation, evaluation of reach and attrition and qualitative feedback from children, school staff and parents. Results: At 12 months there was a difference in the adjusted mean RCADS scores for health-led FRIENDS compared with school-led FRIENDS [-3.91, 95% confidence interval (CI) -6.48 to -1.35] and for health-led FRIENDS compared with usual school provision (-2.66, 95% CI -5.22 to -0.09). At 24 months we were able to assess only 43.6% of our cohort. There were few differences in baseline characteristics between completers and non-completers. Child-reported anxiety in all three groups had reduced by 24 months and there were no longer any group effects. There were no between-group effects for any parent- or child-completed secondary outcomes at 12 or 24 months. The cost of the FRIENDS programme was £52-56 per child. We found no evidence that the FRIENDS programme was cost-effective over a 6-month period; however, our subgroup for the economic analysis differed significantly from our main trial cohort. Conclusions: Although greater reductions in anxiety were noted at 12 months when the FRIENDS programme was delivered by health leaders, these additional benefits were not maintained at 24 months. Children's anxiety levels improved irrespective of the intervention that they received. Our economic evaluation and 24-month assessment had significant shortcomings. However, the universal delivery of specific anxiety prevention programmes will result in additional costs that may be beyond the finances available to most schools. Future work should identify the active ingredients and potential moderators of universal anxiety programmes to determine whether programme length can be reduced, short-term effectiveness maintained and cost-effectiveness improved. At present, our results find limited evidence to support the universal provision of specific anxiety prevention programmes in UK primary schools. Trial registration: Current Controlled Trials ISRCTN23563048. Funding: The National Institute for Health Research Public Health Research programme.